Toward a comparative understanding of beat perception and synchronization - Marc F Schmidt; Michael Kaplan (BMC Neuroscience)
Abstract BPS provides unique opportunities for comparative studies to understand the mechanism(s) of beat perception and its translation into synchronous motor output. We argue that an evolutionary perspective of this behavior will require a clearer dissociation between beat perception and synchronization and a more parameterized approach to studying this behavior.